Diversity, social inclusion and human capital development as fundamentals of financial performance and risk mitigation - Marta-Christina Suciu; Gratiela Georgiana Noja; Mirela Cristea (Amfiteatru Economic Journal, 2020)
The objective of the research undertaken in this paper is to highlight the importance of gender and cultural diversity, social inclusion and both personal and professional development of the employees, in order to mitigate the risks faced by companies, such as to improve the profitability and, correspondingly, to increase their financial performance. The research methodology is based on two modern analysis procedures, namely: multifactorial econometric models, processed by robust regression with Huber and biweight iterations, alongside with structural equation models, configured to highlight global influences in a pre-settled frame of interdependencies among variables. The analysis is performed for a number of 1722 companies with the headquarters in Europe, using data extracted from the Thomson Reuters Eikon (2020) database. The results obtained highlight significant direct influences, both favorable and unfavorable, on the financial performance of European companies, generated by incorporating the fundamental elements and processes of human capital management, diversity and inclusion. At the same time, the empirical analysis reveals that there are risks related to the sustainability of the financial performance of the European companies, whose mitigation requires the adoption of complex strategies to reconsider the efforts of inclusion, but also of those dedicated to reduce the controversies regarding the diversity of personnel, wages, promotion and working conditions.
Keywords: C30; D22; G30; J24; 330; Gender and cultural diversity; inclusion; human capital; financial performance; risks; econometric procedures; strategies